Skin disease prevalence study in schoolchildren in rural Côte d'Ivoire: Implications for integration of neglected skin diseases (skin NTDs). - Rie Roselyne Yotsu; Kouamé Kouadio; Bamba Vagamon; Konan N'guessan; Amari Jules Akpa; Aubin Yao; Julien Aké; Rigobert Abbet Abbet; Barbine Tchamba Agbor Agbor; Roger Bedimo; Norihisa Ishii; L Claire Fuller; et al. (Public Library of Science (PLoS), 2018)
Early detection of several skin-related neglected tropical diseases (skin NTDs)-including leprosy, Buruli ulcer, yaws, and scabies- may be achieved through school surveys, but such an approach has seldom been tested systematically on a large scale in endemic countries. Additionally, a better understanding of the spectrum of skin diseases and the at-risk populations to be encountered during such surveys is necessary to facilitate the process.We performed a school skin survey for selected NTDs and the spectrum of skin diseases, among primary schoolchildren aged 5 to 15 in Côte d'Ivoire, West Africa. This 2-phase survey took place in 49 schools from 16 villages in the Adzopé health district from November 2015 to January 2016. The first phase involved a rapid visual examination of the skin by local community healthcare workers (village nurses) to identify any skin abnormality. In a second phase, a specialized medical team including dermatologists performed a total skin examination of all screened students with any skin lesion and provided treatment where necessary.Of a total of 13,019 children, 3,504 screened positive for skin lesions and were listed for the next stage examination. The medical team examined 1,138 of these children. The overall prevalence of skin diseases was 25.6% (95% CI: 24.3-26.9%). The predominant diagnoses were fungal infections (n = 858, prevalence: 22.3%), followed by inflammatory skin diseases (n = 265, prevalence: 6.9%). Skin diseases were more common in boys and in children living along the main road with heavy traffic. One case of multi-bacillary type leprosy was detected early, along with 36 cases of scabies. Our survey was met with very good community acceptance.We carried out the first large-scale integrated, two-phase pediatric multi-skin NTD survey in rural Côte d'Ivoire, effectively reaching a large population. We found a high prevalence of skin diseases in children, but only limited number of skin NTDs. With the lessons learned, we plan to expand the project to a wider area to further explore its potential to better integrate skin NTD screening in the public health agenda.